FAMILY HEALTH STRATEGY AND FACING VIOLENCE AND RISK FACTORS - Beretta, Regina Celia de Souza (2019)
The Brazilian health movement marked the 1980s and was based on the right of every citizen, on the principles of universality and integrality, with preventive and curative actions integrated into a single decentralized management system: the Unified Health System (SUS). In 1999, the Family Health Strategy was created, differentiating itself by broadening the concept of health promotion and by organizing, orienting, seeking answers and contributing to the health system. This research is qualitative and was based on a bibliographical and documentary survey, in the platforms Google Scholar, Pepsic, Redalyc and Scielo, by means of descriptors: Family Health Strategy, Unified Health System, health promotion, violence and risk factors. After reading the articles, it was observed that the actions of the Health Strategy program can have an effective impact on the living conditions of the population, when they act in the intersectorial dimension with the education and health policies, achieving greater involvement and social participation of the local community. It is possible to say that the field of health becomes viable in a relation between law and social justice.